A framework to understand the social impacts of agricultural trade - Schaafsma, M.; Dreoni, I.; Ayompe, L.M.; Egoh, B.N.; Ekayana, D.P.; Favareto, A.; Mumbunan, S.; Nakagawa, L.; Ngouhouo-Poufoun, J.; Sassen, M.; Uehara, T.K.; Matthews, Z. (Wiley, 2023)
While international trade in agricultural commodities can spur economic development especially where governance is strong, there are also concerns about the local impacts of commodity production and their distribution. Previous frameworks have primarily focused on trade effects on environmental conditions in production regions, as well as economic growth and food security. Instead, we develop a conceptual framework for understanding the impact of agricultural trade on multidimensional wellbeing and equity. The purpose of the framework is to guide the analysis of the impacts of trade on people, by identifying the core concepts and organising the complexity of the local social impacts of global value chains. The framework is supported by evidence from studies on trade in soy, coffee, cocoa, and palm oil.